6(2x+4)=3x-6

Simple and best practice solution for 6(2x+4)=3x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x+4)=3x-6 equation:


Simplifying
6(2x + 4) = 3x + -6

Reorder the terms:
6(4 + 2x) = 3x + -6
(4 * 6 + 2x * 6) = 3x + -6
(24 + 12x) = 3x + -6

Reorder the terms:
24 + 12x = -6 + 3x

Solving
24 + 12x = -6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
24 + 12x + -3x = -6 + 3x + -3x

Combine like terms: 12x + -3x = 9x
24 + 9x = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
24 + 9x = -6 + 0
24 + 9x = -6

Add '-24' to each side of the equation.
24 + -24 + 9x = -6 + -24

Combine like terms: 24 + -24 = 0
0 + 9x = -6 + -24
9x = -6 + -24

Combine like terms: -6 + -24 = -30
9x = -30

Divide each side by '9'.
x = -3.333333333

Simplifying
x = -3.333333333

See similar equations:

| x+9+x+67+76+50=360 | | ihate=maths | | 3e^3x/2=962 | | 0.625(8X+24)+1=0.5(12X-2)+12 | | -16=2y+2 | | 5x-2+x+6= | | 3h-9=5+5h | | -7x+-8y=28 | | 2(x-5)+4=0 | | -3x+8=-7+2x | | 2x-16=4x+2 | | 5-7x=19+7x | | -2(3Y-5)=-8 | | 2x+73=8x-11 | | -18=2a | | 6m^2+9m-6=0 | | 13x-6=9x+14 | | 3x+10+40= | | 10x/y | | -3(-7+m)= | | 3x-5=137 | | 17x=5y+1 | | -4a^2-45a-50=0 | | x+48=x | | 8v+13=3v+18 | | 3x+40+10=180 | | 6(2x+4)=3(8+4x) | | x^-3/2=0 | | 6x-5y+3=-27 | | 9cot^2x+1=4 | | X^3-4x^2-14x-60=0 | | 3x+10+40=360 |

Equations solver categories